Securities Auctions under Moral Hazard: An Experimental Study - Kogan, Shimon; Morgan, John (Review of Finance, 2010)
Abstract In many settings, including venture capital financing, mergers and acquisitions, and lease competition, the structure of the contracts over which firms compete differs. Furthermore, the structure of the contract affects the future incentives of the firm to engage in value-creating activities by potentially diluting effort or investment incentives. We study, both theoretically and in the lab, the performance of debt and equity auctions in the presence of both private information and hidden effort. We show that the revenues to sellers in debt and equity auctions differ systematically depending on the returns to entrepreneurial effort. Using a controlled laboratory experiments we test the model's predictions and find strong support for the theory.